PENGEMBANGAN E-FLIPBOOK TERHADAP PENTINGNYA SEX EDUCATION REMAJA TINGAT SEKOLAH MENENGAH PERTAMA (SMP) - Muhammad Farhan Afandes; Nelyahardi Nelyahardi; Dinny Rahmayanty (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This research is a research and development (R&D) study. R&D is a research model that is in the nature of developing new products or improving existing products through systematic standardization procedures, repeated revisions, and measurements in order to produce better products than before (Sutja et al., 2017). The subjects in this study were grade IX students of SMPN 11 Kota Jambi to test the e-flipbook and 6 BK teachers of SMPN 11 Kota Jambi for product validation. The results of this study indicate that the product can be used as a reference for BK teachers in choosing e-flipbooks for the implementation of information services. This is evidenced by the percentage value of media experts 76% and material experts 80% who are both in the